Experiences of clinical psychologists working in palliative care: A qualitative study. (5th January 2020) - Cramond, Laura; Fletcher, Ian; Rehan, Claire
Abstract: Background: Compassion fatigue refers to the emotional and physical exhaustion felt by professionals in caring roles, whereas compassion satisfaction encompasses the positive aspects of helping others. Levels of compassion satisfaction and fatigue have been found to be inconsistent in palliative care professionals, which could have serious implications for patients, professionals and organisations. Objectives: This study explored the experiences of clinical psychologists working in palliative care, all worked with adults with cancer, to gain an understanding of the impact this work has on their self and how they manage this. Methods: A qualitative approach was taken, using semi‐structured interviews and interpretative phenomenological analysis. Results: Three superordinate themes were identified: commitment, existential impact on the self and the oracle. The participants' experiences were characterised by the relationship between themselves and their patients, the influence of working in palliative services on their world view and the impact of organisational changes. Differences between working as a clinical psychologist in palliative care versus non‐palliative settings were considered. Conclusions: Professionals working in palliative care should be supported to reflect on their experiences of compassion and resilience, and services should provide resources that facilitate staff to practice positive self‐care to maintain their well‐being.